Gene Variants That May Enhance the Effectiveness of Non-Hodgkin Lymphoma Therapy: Genomic and Bioinformatics Approaches - Gustinanda, Rizky; Irham, Lalu Muhammad; Supadmi, Woro; Amukti, Danang Prasetyaning; Adikusuma, Wirawan; Chong, Rockie; Satria, Rahmat Dani; Khair, Riat El (Scripta Medica, 2026)
Background/Aim: Non-Hodgkin lymphoma (NHL) is a cancer of the lymphatic system with a high incidence rate globally. Patient responses to therapies such as chemotherapy and immunotherapy often vary, which is thought to be related to individual genetic differences. The development of genomic and bioinformatic technologies allows the identification of gene variants that play a role in the effectiveness of therapy, thus opening up opportunities for personalised treatment of NHL. This study aimed to identify genetic variants that have the potential to improve the effectiveness of therapy in NHL patients.Methods: This study used a bioinformatics approach to analyse genetic and clinical data available in several database sources, including PharmGKB, Haploreg v4.2, GTEx Portal and Ensembl.Results: This study identified two significant genetic variants, rs396991 in the FCGR3A gene and rs3957357 in the GSTA1 gene, that play a role in improving the effectiveness of NHL therapy. The rs396991 variant showed increased affinity to IgG1 and effectiveness of antibody-dependent cellular cytotoxicity (ADCC) mechanism in rituximab therapy. Meanwhile, the rs3957357 variant in GSTA1 was associated with better event-free survival in patients receiving R-CHOP chemotherapy. High expression of FCGR3A gene in immune tissues and GSTA1 gene in liver also reinforced its biological role in therapy response.Conclusions: Genetic variations in FCGR3A (rs396991) and GSTA1 (rs3957357) have potential as predictive biomarkers of R-CHOP therapy effectiveness in NHL patients. These findings support the application of genetic analysis as a basis for more personalised and effective therapeutic strategies in the treatment of NHL.